2015
DOI: 10.1111/ipd.12199
|View full text |Cite
|
Sign up to set email alerts
|

The post‐traumatic colour change of primary incisors: a colourimetric and longitudinal study

Abstract: The earlier recovery of a* was followed by the recovery of L*. During the post-traumatic period, ΔE*ab failed to reach the clinically acceptable threshold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
2
0
3
Order By: Relevance
“…Crown discoloration occurring more than 3 months following TDI had a higher incidence of pulp necrosis with subsequent infection of the root canal system. Previous studies have shown that discoloration may either occur shortly after trauma or delayed color change can be observed . There is a risk of bias in determining the elapsed time between an injury and the discoloration.…”
Section: Discussionmentioning
confidence: 99%
“…Crown discoloration occurring more than 3 months following TDI had a higher incidence of pulp necrosis with subsequent infection of the root canal system. Previous studies have shown that discoloration may either occur shortly after trauma or delayed color change can be observed . There is a risk of bias in determining the elapsed time between an injury and the discoloration.…”
Section: Discussionmentioning
confidence: 99%
“…A mudança de cor varia de acordo com o tipo de sequela que o dente desenvolve. Sob essa ótica, a coloração dentária pode ser um indicador na identificação do tipo de complicação dentária pós-traumática, sugerindo a existência de uma associação entre o tipo de lesão e a ocorrência de descoloração coronária (LOPES et al, 2020;HYUN;SHIM;KIM, 2016;FONTENELE et al, 2017). Em relação à associação entre o tipo de lesão e as sequelas encontradas em dentes decíduos traumatizados, a concussão, a subluxação e a luxação lateral foram as LDTs mais associadas à descoloração dentária pós-traumática (LOPES et al, 2020).…”
Section: Resultsunclassified
“…Sendo assim, malformação dentária, dentes impactados e distúrbios de erupção na dentição permanente são algumas das consequências que podem ocorrer após lesões na dentição decídua e/ou osso alveolar (Malmgren et al, 2012). Além disso, estudos anteriores relataram que mais de 50% dos dentes decíduos traumatizados apresentam modificação de cor (Hyun et al, 2016 (Pelotas, RS, Brasil). Nas lesões de subluxação, mais de 50% dos casos de modificação de cor da coroa, cálculo pulpar, fístula e reabsorção radicular inflamatória ocorreram dentro de 180 dias após o TDA.…”
Section: Tratamentounclassified
“…Segundo Hyun et al (2016) a descoloração da coroa dentária acontece em decorrência da hemorragia intrapulpar que ocorre como resultado das lesões traumáticas. Após a hemorragia é formada hemoglobina, a partir da degradação da hemoglobina é formada hemossiderina que penetra nos túbulos dentinários alterando a cor do dente.…”
Section: Prognóstico E Complicaçõesunclassified